New Warsaw, occupation lab or nest of terrorists?: the Gaza Strip and the bare life (Tempo e Argumento, 2012)
Since 2005, when Israeli government withdrew its settlers and military from the Gaza Strip, the Palestinian territory was increasingly isolated and surrounded and their inhabitants subjected to collective punishment and violent death. The Israeli security policy regarding the Strip, officially adopted to curb Palestinian terrorism, has culminated in a long-suffering for the local population as a whole, who see their living conditions deteriorate to the extent that there is an overall deprivation of goods and services basic. Removing the simplifying official discourse of the war on terror, in this context in which violence was even more commonplace, we seeks to analyze the relevance of thinking Gaza from concepts who consider politics in modernity, as imunitas, field and homo sacer. The article summarizes these concepts by checking, based on testimonies and reports of nongovernmental organizations, their contribution to the understanding of the particular case.
Keywords: occupied palestinian territories; culture of impunity; Israel; homo sacer; unilateral disengagement